Outbreak of infectious pododermatitis in a sheep flock in southern Bahia: Case report - Costa, Lorrana; Santana , Maria Antonia Oliveira; Araújo Nunes , Victor; Almeida , Kailly Santos de (Pubvet, 2025)
Northeastern Brazil, particularly the state of Bahia, stands out in sheep farming due to its local climate and vegetation, which favor the adaptation of these animals. This activity is advantageous for small-scale producers, as it involves low costs and offers ease of commercialization. In 2023, Bahia accounted for 23% of the national sheep herd, establishing itself as the leading producer. However, diseases affecting these animals, such as infectious pododermatitis, cause significant economic losses due to reduced forage intake, decreased weight gain, and infertility. Pododermatitis, caused by bacteria such as Dichelobacter nodosus and Fusobacterium necrophorum, is one of the most common diseases among goats and sheep. It leads to hoof inflammation resulting in severe lameness, and can seriously compromise the animals' health, potentially leading to death. To address this issue, the Bahia State Agricultural Defense Agency (ADAB) implemented the State Program for the Health of Goats and Sheep (PESCO), aimed at controlling and eradicating such diseases. This article aims to describe an outbreak of infectious pododermatitis in a flock in southern Bahia, discussing its etiology, epidemiology, pathogenesis, clinical signs, and diagnosis, as well as emphasizing the importance of prophylactic measures for disease control and the prevention of economic losses.
Keywords: Bahia; hoof; sheep; pododermatitis; prevention